2014
DOI: 10.1039/c3an01832f
|View full text |Cite
|
Sign up to set email alerts
|

Effect of substrate choice and tissue type on tissue preparation for spectral histopathology by Raman microspectroscopy

Abstract: Raman spectroscopy is a non-destructive, non-invasive, rapid and economical technique which has the potential to be an excellent method for the diagnosis of cancer and understanding disease progression through retrospective studies of archived tissue samples.Historically, biobanks are generally comprised of formalin fixed paraffin preserved tissue and as a result these specimens are often used in spectroscopic research. Tissue in this state has to be dewaxed prior to Raman analysis to reduce paraffin contribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
48
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 34 publications
0
48
0
Order By: Relevance
“…A 100x water immersion objective (LUMPlanF1,Olympus,N.A. : 1.0) was used to focus the laser on the sample, immersed in distilled water, providing a spatial resolution of ~1μm (Fullwood et al, 2014;.…”
Section: Raman Spectroscopy Measurementsmentioning
confidence: 99%
“…A 100x water immersion objective (LUMPlanF1,Olympus,N.A. : 1.0) was used to focus the laser on the sample, immersed in distilled water, providing a spatial resolution of ~1μm (Fullwood et al, 2014;.…”
Section: Raman Spectroscopy Measurementsmentioning
confidence: 99%
“…However, it may be argued that greater consistency of spectral information is achieved when sections are deparaffinised. Deparaffinising also allows post-staining of the sections, although it has been demonstrated that the efficiency of the deparaffinisation process can depend on the tissue pathology [32]. Nevertheless, it can also be argued that, even for research purposes, protocols for such tissue processing should be maintained as close as possible to those currently employed in the clinical environment.…”
Section: Introductionmentioning
confidence: 99%
“…However, it may be argued that greater consistency of spectral information is achieved when sections are deparaffinised. Deparaffinising also allows post-staining of the sections, although it has been demonstrated that the efficiency of the deparaffinisation process can depend on the tissue pathology [23].…”
Section: Future Perspectivesmentioning
confidence: 99%
“…The x, y co-ordinates of each recorded cell were saved and, after Raman recording at 532 nm, the slides were Pap stained and each cell was revisited to verify whether it was a superficial, intermediate, parabasal or white blood cell. Spectroscopic substrates, such as calcium fluoride, are commonly used for research purposes and although they reduce the presence of confounding contributions of the substrate [22][23][24], they are considerably more expensive and thus not really a viable choice for population screening applications such as cervical cancer screening. Although 785 nm is commonly used for biological applications of Raman spectroscopy, glass shows a strong background at this wavelength so to use glass as a substrate for Raman spectroscopy, spectra must be recorded using shorter wavelengths such as 532 nm.…”
Section: Raman Spectroscopy For Cytopathologymentioning
confidence: 99%